Moving from coproduction to commonization of digital public goods and services. - Shulz, Sébastien (Public Administration Review, 2025)
The hybridization of digital commons and public administration institutions led by bureaucratic entrepreneurs is a relatively recent phenomenon that has received limited attention in the literature. The term coined to describe this evolution is the "commonization" of digital public goods and services. I define commonization as the integration of shared property, peer production, and self‐governance into public administration. To explore the democratizing potential of commonization, I conducted a qualitative study comparing two case studies in France and Spain (Barcelona). My approach involves 44 semistructured interviews and online observations analyzed through the analytical framework of institutional work. The findings highlight five factors that enhance, and two that hinder, citizen power in co‐governance arrangements. In conclusion, I identify the theoretical and practical implications of commonizing digital public goods and services, providing valuable insights for practitioners and scholars, particularly in the New Public Governance paradigm.